2019
DOI: 10.1055/a-1031-9832
|View full text |Cite
|
Sign up to set email alerts
|

The FUSION iENA Study: Comparison of I-124-PET/US Fusion Imaging with Conventional Diagnostics for the Functional Assessment of Thyroid Nodules by Multiple Observers

Abstract: Aim To investigate the value of I-124 positron emission tomography (PET) / ultrasound (US) fusion imaging in comparison to conventional diagnostics (CD) of Thyroid nodules (TN) by multiple observers. Methods Digital patient case files (PCF) of patients that received CD and I-124-PET/US in clinical routine were prepared containing cine-loops of the examinations. All physicians with nuclear medicine specialty from Germany, Austria, and Switzerland were invited to participate. 106 acquired observers com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 36 publications
0
14
0
4
Order By: Relevance
“…Patient data of a previous study, named “ F usion U ltra S ound I maging o f the Thyroid Gla N d with I -124 PET— E valuation of N odule A llocation. ( FUSION iENA )” were further evaluated [ 28 ]. Adult patients who were referred to a university hospital for clinical routine thyroid diagnostics between February 2015 and February 2017 and, who gave informed consent for additional I-124-PET/US fusion imaging in case of uncertain findings in conventional diagnostics (CD) and for the usage of their data for future research, were included.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient data of a previous study, named “ F usion U ltra S ound I maging o f the Thyroid Gla N d with I -124 PET— E valuation of N odule A llocation. ( FUSION iENA )” were further evaluated [ 28 ]. Adult patients who were referred to a university hospital for clinical routine thyroid diagnostics between February 2015 and February 2017 and, who gave informed consent for additional I-124-PET/US fusion imaging in case of uncertain findings in conventional diagnostics (CD) and for the usage of their data for future research, were included.…”
Section: Methodsmentioning
confidence: 99%
“…In order to overcome this limitation and to achieve accurate functional characterizations of TN, hybrid imaging approaches such as sensor-navigated Tc-99m-pertechnetate single photon emission computed tomography (SPECT)/US and sensor-navigated sodium iodine-124 (I-124) positron emission tomography (PET)/US have been introduced [ 24 , 25 , 26 , 27 ]. Particularly, I-124-PET/US proved to be superior in comparison to the conventional diagnostics (CD), comprising B-mode US and Tc-99m-pertechnetate scintigraphy, in a multi-observer study with >100 nuclear medicine physicians [ 28 ]. The results of this study showed that the confidence in functional assessment of TN increases significantly when I-124-PET/US is added to CD.…”
Section: Introductionmentioning
confidence: 99%
“…In der FUSION iENA Studie aus dem Jahr 2019 [51] Die bisherigen Studienergebnisse anhand einer Auswahl von 34 Patienten mit schwieriger topografischer Korrelation von sonografisch identifizierten Schilddrüsenknoten mit dem Szintigramm zeigen, dass insbesondere der Anteil von hypofunktionellen, aber auch der kleiner hyperfunktioneller Knoten in der konventionellen Diagnostik unterschätzt zu sein scheint. Zudem bestehen v. a. bei ungünstig lokalisierten Knoten (z.…”
Section: Spectunclassified
“…B. randständig oder dorsal im Schilddrüsenparenchym) häufig Unsicherheiten hinsichtlich der szintigrafischen Charakterisierung, was zu einer relevanten Interobserver-Variabilität führen kann. Hinsichtlich der genannten Limitationen zeigten sich hochsignifikant bessere Ergebnisse, wenn eine ergänzende [ 124 I]-PET/US-Fusionsbildgebung durchgeführt wurde [51,52]. So konnten z.…”
Section: Spectunclassified
See 1 more Smart Citation